Analysis of The Technology Acceptance Model (TAM) on The Motivation of Aparatur Sipil Negara (ASN) Threatened by Early Retirement in Adopting Technology in Blora Regency - Soegiyatno, Furqon Ahmadi; Harsono, Mugi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the moderating role of Perceived Threat of Early Retirement (PTER) within the Technology Acceptance Model (TAM) on older civil servants’ (ASN) intention to use technology in Blora Regency, amid dismissal threats under Law No. 20/2023. Using a survey and PLS-SEM analysis, results show Attitude Towards Using Technology does not significantly affect Intention to Use Technology. PTER also does not moderate this relationship but weakly moderates the link between Perceived Usefulness and Intention. These findings suggest interventions are needed to strengthen perceived usefulness to support ASNs’ career sustainability.